Information Systems Design and Intelligent Applications Proceedings of Fourth International Conference INDIA 2017 - Bhateja, Vikrant; Nguyen, Bao Le; Nguyen, Nhu Gia; Satapathy, Suresh Chandra; Le, Dac-Nhuong (Advances in Intelligent Systems and Computing, 2018)
The book is a collection of high-quality peer-reviewed research papers presented at International Conference on Information System Design and Intelligent Applications (INDIA 2017) held at Duy Tan University, Da Nang, Vietnam during 15-17 June 2017. The book covers a wide range of topics of computer science and information technology discipline ranging from image processing, database application, data mining, grid and cloud computing, bioinformatics and many others. The various intelligent tools like swarm intelligence, artificial intelligence, evolutionary algorithms, bio-inspired algorithms have been well applied in different domains for solving various challenging problems.